Integration of PhET Simulation Technology in LKPD: An Innovative Solution to Improve Students' Understanding of Physics Concepts - Irwan Rahmani, Anas; Munandar, Aris; Nurhikmah,; Sundari, Dewi Tri (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to find out: 1) how to describe students' understanding of concepts before being taught using LKPD based on PhET simulation, 2) to find out how to understand students' concepts after being taught using LKPD based on PhET simulation, 3) to find out if there is an increase in students' understanding of concepts before and after being taught using LKPD based on PhET simulation for students of the Physics Education Study Program of UIN Alauddin Makassar 2024. This type of research is pre-experimental with a one-group pretest-posttest desing design. The subjects of this research are all students of the Semester I of the Physics Education Study Program of UIN Alauddin Makassar Odd Semester 2024/2025. The sampling technique uses purposive sampling. The instrument used is a question to measure understanding of the concept. The results of the descriptive analysis show that the average score of the concept comprehension score before using the LKPD based on PhET simulation , the tcount obtained is 5.43 and the ttable obtained is 2.08.